2020
DOI: 10.29173/cjnser.2020v11n1a372
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: The Prospects for Nonprofit Human Resource Management

Abstract: This article explores the impacts of COVID-19 on nonprofit employees and human resource management (HRM). The pandemic is wreaking havoc on people’s health and well-being and threatening the primary institutions that support the functioning of society. For nonprofits, COVID-19 is a call to action at many levels. As the devasting impacts of the pandemic evolve, nonprofits have continued to provide essential services and help the vulnerable. At the same time, the impacts of COVID-19 portend serious and potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Johnson Avery and Kim (2009) noted a general tendency of health agencies such as the WHO and the CDC to make reference to governmental and public partners and exclude private sector organizations in their press releases. On the contrary, previous research and empirical evidence have suggested that NGOs have played a key role providing critical services to those in need during the COVID-19 pandemic, especially to socially vulnerable groups ( Akingbola, 2020 ). Thus, it seems reasonable to conclude that engaging more frequently with NGOs may increase the health agencies’ understanding of different social groups and help NGOs cater to vulnerable groups they serve.…”
Section: Discussionmentioning
confidence: 96%
“…Johnson Avery and Kim (2009) noted a general tendency of health agencies such as the WHO and the CDC to make reference to governmental and public partners and exclude private sector organizations in their press releases. On the contrary, previous research and empirical evidence have suggested that NGOs have played a key role providing critical services to those in need during the COVID-19 pandemic, especially to socially vulnerable groups ( Akingbola, 2020 ). Thus, it seems reasonable to conclude that engaging more frequently with NGOs may increase the health agencies’ understanding of different social groups and help NGOs cater to vulnerable groups they serve.…”
Section: Discussionmentioning
confidence: 96%
“…First, NPOs have relied on human capital to sustain themselves during the crisis (Akingbola, 2020 ), but working and volunteering conditions have deteriorated. Second, the economic and financial fragility of the nonprofit sector has worsened due to the loss of stable resources (Finchum-Mason et al, 2020 ; Johnson et al, 2020 ; Kim & Mason, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given their placement between the state and civil society, nonprofit service-providing organizations are critical for service users as they provide vital services, facilitate social connections, and promote a measure of well-being for members of their communities (Akingbola, 2020;Milbourne, 2013). The three organizations studied here are also important places of employment for people with disabilities, who can develop their capacities, build social capital, and contribute to their communities.…”
Section: Resultsmentioning
confidence: 99%